An Indirect Effect Analysis of Tourism Public Expenditure on Tourist Arrivals through Infrastructure, Accessibility, and Room Occupancy: A WarpPLS Study in Java and Bali - Dafa Afif Pratama; Fafurida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The growth of the tourism sector in Indonesia depends not only on promotional efforts but also on the quality of infrastructure, destination accessibility, and supporting facilities. This study aims to analyze the indirect effect of Tourism Public Expenditure on tourist arrivals through the mediating roles of infrastructure, accessibility, and hotel room occupancy. Secondary data were collected from the Central Statistics Agency and the Ministry of Tourism for the Java and Bali regions over the 2015–2023 period. The analysis was conducted using Structural Equation Modeling with WarpPLS software. The results indicate that government spending positively influences infrastructure development and improvements in accessibility. In turn, infrastructure and accessibility significantly affect hotel room occupancy, which ultimately has a substantial impact on tourist arrivals. The influence of Tourism Public Expenditure on tourist arrivals is therefore indirect, mediated through these pathways. These findings highlight the importance of effective government spending in laying the foundation for sustainable tourism growth. Keywords: Tourism Government Spending, Infrastructure, Accessibility, Room Occupancy, Tourist Arrivals